Barbed sutures reduce arthrotomy closure duration and suture utilisation compared to interrupted conventional sutures for primary total hip arthroplasty: a randomised controlled trial. Issue 5 (September 2021) - Sundaram, Kavin; Piuzzi, Nicolas S.; Klika, Alison K.; Molloy, Robert M.; Higuera-Rueda, Carlos A.; Krebs, Viktor E.; Mont, Michael A.
Introduction: The broad aim of this study was to compare the safety and efficacy of using barbed sutures and running closure versus interrupted placement of standard of care sutures for closure of the arthrotomy during total hip arthroplasty (THA). Specifically, we compared duration of arthrotomy closure, the number of sutures utilised for arthrotomy closure, and 90-day outcomes including wound-related readmission, reoperation, and complications. Methods: A total of 60 patients undergoing 60 THAs were enrolled in a prospective, single-blinded trial and randomised to receive either running closure of the arthrotomy with barbed sutures ( n = 30) or interrupted closure with standard of care sutures ( n = 30). Patients were eligible if they were undergoing primary THA for osteoarthritis and excluded if they had a BMI > 45 kg/m 2 or age > 80 years or <18 years. Results: Arthrotomy closure duration was significantly shorter in the barbed suture group (3 minutes ± 9 seconds) versus the standard of care group (8 minutes ± 26 seconds, p < 0.001). The suture utilisation for arthrotomy closure was 1 suture in the barbed sutured group 28/30 (93%) patients versus 2–4 sutures in 27/30 (90%) in the standard of care group ( p < 0.001). The overall number of wound-related complications in the barbed suture group was 1/30 (3%) versus 1/30 (3%) in the standard of care group ( p = 1.00). The rate of suture abscesses was 1/30 (3%) in barbed suture group versus the standard of care ( p = 1.00). There was trochanter bursitis 1/30 (3%) in the standard of care group versus zero in the barbed suture group ( p = 1.00). Conclusions: These results suggest that barbed suture utilisation may be faster and more resource efficient than use of standard of care sutures for arthrotomy closure in THA. ClinicalTrials.gov Identifier: NCT03285555